Semiotic Representation of Gender in Google Emojis - Nazia Kalsoom; Sadia Kalsoom (Linguistics and Literature Review, 2019)
Modern technology has undoubtedly changed the way we communicate. Emoji is the latest development that crosses all language barriers and serves as a global language. The present study seeks to investigate how gender is semiotically represented in Google female emojis. The study is interpretive and qualitative in nature. By using Kress & Leeuwen (2006) the Grammar of Visual Design model, the study analyzed the stereotypical and professional (newly introduced) Google emojis for female and attempted to spot the tenets of liberal feminist movement. The revision of emojis by Google, with a belief that ‘this will empower young women and better reflect the pivotal roles women play in the world’ bespeaks the flourishing global liberal feminist movement. This acknowledgement is a feather in liberal feminist movement’s cap in that gender roles are considered social constructs. The new emojis duly construct women as coming out of the stereotypical womanish stuff and entering into professions that were once male-dominant.